Distribution and microbial degradation of dissolved organic carbon in the northern South China Sea - Ding, Ling; Shan, Sen; Luo, Chunle; Wang, Xuchen (Frontiers in Marine Science, 2022)
Dissolved organic carbon (DOC) is the largest reduced carbon pool in the ocean, and it plays significant roles not only in the ocean carbon cycle but also in the control of many biogeochemical processes in the ocean. We present the concentrations and distribution of DOC in the northern South China Sea (SCS) and western North Pacific (NP) in the spring and summer seasons of 2015-2016 and 2019. Laboratory incubation bioassay experiments were also conducted to determine the microbiological respiration of DOC. In the SCS, the concentrations of DOC varied within a range of 38-95 μM, and the large spatial variations in DOC in the upper 100 m depth were influenced by a combination of factors, including primary production, terrestrial inputs from the Pearl River and the intrusion of the Kuroshio Current. The mesopelagic DOC distribution in the northern SCS basin was largely influenced by the physical mixing of upwelled deep water; however, biological processes were estimated to account for 6-20% of the modulation in DOC concentrations. Compared with the deep DOC levels in open ocean areas, a slightly excessive DOC concentration (~ 3-4 μM) was observed in the deep water of the SCS basin. Approximately 10-20% of the DOC was consumed by mesopelagic and/or deep water bacteria in the incubation bioassay experiments, and labile DOC was preferentially respired, resulting in decreased δ13C and Δ14C values of DOC.